KEDUDUKAN HUKUM YAYASAN YANG DIALIHKAN SECARA HIBAH (Studi Kasus Yayasan Jala Nanggala Kota Malang) - Amethystia, Adisresti (Universitas Muhammadiyah Surabaya, 2021)
Foundation is a legal entity with social character, consisting of wealth that is cruel and intended to achieve certain purposein the social, religious and humanity fields. Among these objectives are the implementation of higher education. With this social character, a foundation cannot be owned by anyone except by himself. A foundation as legal entity is made the object of a grant agreement, the agreement is null and void because an obyektif conditions are not fulfilled, so the grant is deemed to have never existed. The legal issue in this research is the Jala Nanggala Foundation's juridical position which is transferred by means of a grant. This legal standing will be analyzed through: first, the juridical position of the foundation as a legal consequence of the transfer of the foundation on a grant basis. Second, juridical efforts to restore or save the Jala Nanggala Foundation which was transferred by means of a grant. This research was conducted using the sosio legal method, with a conceptual approach and a statutory approach. The results of this study indicate that the position of the Jala Nanggala Foundation which was transferred by grant is still a legal entity as at the time it was founded and obtained approval from the Minister of Law and Human Rights, but is vacuum in its operations. Four alternative juridical efforts were found to restore or save the Jala Nanggala Foundation and the School of Economics under its auspices. Notaries have a decisive role and responsibility in juridical efforts to restore or save the foundationKeywords: foundations, grants, notary